2017
DOI: 10.2135/cropsci2016.04.0284
|View full text |Cite
|
Sign up to set email alerts
|

Early Seedling Growth Characteristics Relate to the Staygreen Trait and Dhurrin Levels in Sorghum

Abstract: Dhurrin content in leaves of the mature sorghum [Sorghum bicolor (L.) Moench] plant is a quantitative measure of the level of pre‐ and postflowering drought tolerance, with high dhurrin contents expressed in postflowering drought‐tolerant lines. Postflowering drought tolerance in sorghum has been linked to the staygreen trait and associated with increased grain yield during postanthesis stress. Seasonal variability in postflowering drought occurrences makes selection for the staygreen trait unpredictable and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…In sorghum, stay green has for instance been associated with the formation and presence of the cyanogenic glucoside dhurrin (Hayes et�al. 2015, Emendack et�al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In sorghum, stay green has for instance been associated with the formation and presence of the cyanogenic glucoside dhurrin (Hayes et�al. 2015, Emendack et�al. 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in leaf dhurrin content for low-and high-dhurrin lines is only eminent when measured from fully developed leaves of mature plants (Burke et al, 2013). However, Emendack et al (2017) reported greater fresh shoot biomass for high-dhurrin seedlings 10 DAE, grown in nutrient-deficient play sand. In addition, during early seedling development, ?75% of the endosperm sugar content (including glucose, fructose, and sucrose) is depleted by 8 d after sowing (?4 DAE) (Newton et al, 1980).…”
Section: Discusionmentioning
confidence: 93%
“…Coupled with this is the fact that even though cyanogenesis is a stable heritable trait with all individuals in some species being cyanogenic, others can be highly polymorphic, with phenotypically acyanogenic individuals ( Jørgensen et al, 2005a;Zagrobelny et al, 2008). Emendack et al (2017) reported that seedlings of high-dhurrin genotypes have greater fresh shoot biomass than low-level genotypes at 14 DAE when grown in nutrient-deficient play sand at optimum climatic conditions. Thus, there may be very low dhurrin levels or acyanogenic sorghum cultivars in other germplasms.…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…These genotypes maintain green leaf area and hence photosynthetic capability and/or improved translocation of carbohydrates under late season moisture stress, and produce higher grain yields compared with senescent genotypes (Borrell and Douglas, 1997;Borrell et al, 2003). Staygreen genotypes have also been shown to have a comparatively higher level of the secondary metabolite dhurrin (a Cyanogenic glucoside with nitrogen storage function) in leaves of matured plants at the late vegetative stage (Burke et al, 2013), and 10-day old seedlings of staygreen lines showed higher biomass than senescent lines under nitrogen limiting conditions (Emendack et al, 2016).…”
Section: Introductionmentioning
confidence: 99%